Optimalisasi Teknologi Digital dalam Meningkatkan Agility, Tata Kelola di Era Transformasi Digital - Astuti, Wati Aris; Siti Kurnia Rahayu; Ony Widilestariningtyas; Sendi Azahra Angelina (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2025)
In today’s rapidly evolving digital era, organizations must remain responsive to shifting market dynamics and advances in technology. This study examines how digital technology and organizational agility influence corporate governance. Using a quantitative approach, data were gathered through a survey distributed to respondents involved in managing information technology. The data collected were analyzed using simple regression to evaluate the relationships among the variables. The findings reveal that digital technology positively contributes to strengthening governance structures, improving operational efficiency, and supporting data-driven decision-making. Agility is also shown to play a crucial role in fostering governance that is more adaptive and flexible in responding to change. Together, these two factors reinforce one another and support strategic technology management within a dynamic business environment. Overall, the results enrich the literature on governance and provide practical insights for organizations undergoing digital transformation to become more adaptive, accountable, and sustainable.